COVID-19 impact on local agri-food system in Cambodia, Myanmar, and the Philippines: Findings from a rapid assessment - Espino, Apple; Itliong, Kirstein; Ruba, Christine Dianne; Thy, Or; Barbon, Wilson John; Monville-Oro, Emilita; Gummadi, Sridhar; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The COVID-19 pandemic and the subsequent enforcement of mobility restrictions have created bottlenecks in the agri-food system. When the food supply chain is disrupted, economic loss occurs, putting rural households, already in poverty, into severe food insecurity. A survey was conducted to assess the impacts of restrictions brought by COVID-19 on local food systems operations of Climate-Smart Villages (CSVs) in Cambodia, Myanmar, and the Philippines. The rural and traditional food systems of agriculture-based villages continued to operate with minimal adjustments during the course of COVID-19 restrictions. Our findings showed high mean household dietary diversity scores in Chhouk CSV (6.4), Htee Pu CSV (8.2), and Himbubulo Weste CSV (7.2) despite significant perceived changes in the availability and prices of certain food groups. Complementary and diverse food production and access to informal food outlets were essential parts of the local food systems and played critical roles in supplying food commodities to the population during the pandemic.